Pengaruh Distribusi Zakat Produktif terhadap Peningkatan Kesejahteraan Mustahiq melalui Program Microfinance Desa (Studi Kasus pada Badan Amil Zakat Nasional Kabupaten Maros) - Munawwarah Sahib; Nur Husna; Hermin Andi Magga (CV. Creative Tugu Pena, 2024)
Zakat, as one of the pillars of Islam, has great potential in overcoming the problem of poverty. In order for zakat to have a significant influence on the community's economy, the potential of zakat must be optimized. Apart from potential, the distribution of zakat should be prioritized to build productive businesses for zakat recipients that can generate income for them and hopefully contribute to employment. In line with this, BAZNAS established a village microfinance program, namely a non-profit microfinance institution for small entrepreneurs from underprivileged groups. This program empowers the community, especially micro, small and medium enterprises, helps start-up businesses without interest, which can help alleviate poverty. The aim of this research is to determine the effect of productive zakat distribution on the welfare of mustahiq through the village microfinance program at BAZNAS Maros Regency. This research uses quantitative methods. The data analysis techniques used are descriptive respondents, descriptive variables and hypothesis testing. The data was processed using statistical analysis using the SmartPLS version 4 for Windows application. The research results show that productive zakat influences the welfare of mustahiq with a significance level of 0.000<0.05. Through the R2 determination test, it is known that the influence of productive zakat distribution on mustahiq welfare is 80.9% so it can be concluded that productive zakat influences the welfare of mustahiq.